GovChat: A Cornerstone of Digital Government - Mohamed Ali, Faizura Haneem; Nik Mat, Nik Zalbiha; Mat Adam, Roshaimieza (Journal of Emerging Technologies and Industrial Applications, 2022)
The rise of government personnel using external social media platforms as communication platform when dealing with official matters has exposed government communication information to data privacy and security concerns. Due to the urgent need for real-time communication among government personnel in the digital workplace, MAMPU has developed GovChat as the first government messaging platform, which connects the government personnel in a private environment. GovChat is a simple and reliable instant messaging application with built-in security and data storage in Public Sector Data Center (MyGovCloud@PDSA). GovChat is developed tailored to the requirements of government agencies, with basic and advanced features based on emerging technologies, such as chatbots, image processing for watermarking, and calendar integration. GovChat was gradually rolled out to government agencies beginning in July 2021, with approximately 130 agencies participating to date. GovChat is a digital communication platform aims to support the digital government transformation as outlined in MyDIGITAL Blueprint 2021-2030, and Digitalization Strategic Plan for Malaysia Public Sector 2021-2025.